Acquired Ulcero-Mutilating Bilateral Acro-Osteopathy (Bureau-Barrière Syndrome) - Tchernev, Georgi (Open Access Maced J Med Sci, 2017)
We present a 35-year-old male patient with Bureau-Barrière syndrome. Bureau-Barrière syndrome is an ulcero-mutilating acropathy almost invariably associated with excessive alcohol intake. It presents with a triad of trophic skin changes with recurrent ulcerations, bone lesions and nerve damage. The clinical presentation includes chronic painless plantar ulcerations with periulcerous hyperkeratosis, hyperhidrosis, livedoid skin colour, nail dystrophy, widening and infiltration of the toes and common interdigital mycoses. Other non-specific skin changes related to the alcohol consumption are commonly observed as well. The condition affects mainly middle-aged men suffering from alcoholism. Often a bilateral location at the lower limb of male alcoholics has been described, as in our patient. Successful treatment of the Bureau-Barrière syndrome requires an interdisciplinary approach. Cessation of alcohol intake and smoking is of paramount importance.